DIVERSITY OF PROBIOTIC BACTERIAL LECTIN SYSTEMS - M. V. Lakhtin (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
Lectin systems of industrial strains of probiotic bacteria of human origin were investigated. Lectin systems were observed as ceil surface and extracellular; solubilized in mild and firm conditions; solid phased fluorescent and chemiluminescent; anionic/acidic, neutral and cationic/alkaline; masked/biocked/encapsuiated with exopoiymeric substances of non-protein origin (localized together] and non-encapsuiated;genus/strain/consortia-specific and typing; specific to soluble artificial polymeric polyvalent glycoconjugates imitating exposed clusters of mucin-type glycans and possessing exposed multiple carbohydrate residues such asGalNAc-alpha- or Man-alpha- as side short branches of polyacrylamide linear chain). Results indicate prospects of glycoconjugates-binding lectin systems in glycobiology, molecularglyco- medicine and bio(nano)giycotechnoiogy.